Experimental Investigation of the Unsteady Flow Behavior on a Film Cooling Flat Plate. (November 2016) - Rouina, S.; Miranda, M.; Barigozzi, G.
Abstract: An experimental study was conducted to investigate the unsteady behavior of film cooling for cylindrical holes on a flat plate wind tunnel. Tests have been carried out at low speed and low inlet turbulence intensity level, with blowing ratios varied in the range 0.5–1.5. Aerodynamic investigations have been performed through the measurement of discharge coefficients in order to characterize the blowing conditions. A Laser Doppler Velocimetry (LDV) was then used to study the boundary layer behavior just downstream of the holes for variable injection condition. A high resolution PIV system was finally used for flow visualization and flow field measurement to investigate the unsteady mixing process taking place between coolant and main flow. For low blowing ratios, the jet stays close to the surface; traces of coherent vortical structures are detected only far from injection, which appear as clockwise vortices. Increasing the blowing ratio leads to the appearance of counter-clockwise vortical structures due to the breakdown of the Kelvin Helmholtz instability of the shear layers.